Frequência de hábitos alimentares saudáveis em adolescentes do ensino médio de Pelotas / RS - Couto, Shanda de Freitas (2010)
To evaluate the frequency of healthy eating habits among adolescents from high schools in the urban area of Pelotas, based on the "10 Steps to Healthy Eating" from Brazilian Ministry of Health. Methods: A school-based cross-sectional study was conducted, stratified according to school system and proportional to the number of students attending each school. A total of 1233 adolescents (13-19 years) were studied. The "10 Steps to Healthy Eating" were evaluated through a self-administered questionnaire with questions on food frequency and other questions about different aspects included in the 10 Steps. We performed descriptive analysis of the data, followed by bivariate analysis. Results: The average number of steps achieved was 1.8. The majority of the population adhered to one and two steps and only 1.7% reached more than five steps. It is noteworthy that none of the subjects achieved entirely the "10 Steps to Healthy Eating." The recommendation that had the highest frequency of compliance was step four, referring to the consumption of the combination of rice and beans at least five times a week. The recommendations that had lower frequencies of compliance were related to consumption of soft drinks, processed juices, sweets and snacks less than once a week, and step three on the consumption of three servings of vegetables / green leafes and three servings of fruit daily. Conclusion: Adherence to the "10 steps to a healthy diet" recommended by the Ministry of Health by adolescents in Pelotas was very low. Considering the present and future importance of healthy eating in adolescence, it is recommended greater investment in public policies in the area of food and nutrition.